Credit, interest rates, and the open economy : essays on horizontalism - Rochon, Louis-Philippe.; Vernengo, Matias (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 2001)
The horizontalist perspective is an extension of the post-Keynesian approach, hitherto focused on a theory of credit and money. This book extends horizontalism beyond its traditional boundaries to compare and contrast its position with orthodox and non-orthodox views on money.
Includes bibliographical references and index.
rpm 19/08/18
Loans
Keywords: Money supply; Monetary policy; Credit